Standardization guidelines and future trends for PET hydrolase research - Ren Wei; Peter Westh; Gert Weber; Lars M. Blank; Uwe T. Bornscheuer (Nature Communications)
Abstract Enzymatic depolymerization of polyethylene terephthalate (PET) towards monomer recycling offers a green route to a circular plastic economy, with scale-up currently underway. Yet, inconsistent assessment methods hinder clear comparisons between various PET hydrolases. This Perspective aims to identify critical gaps in this dynamic research field and outline key principles for selecting and tailoring novel enzymes, such as using uniform PET samples and standardizing reaction settings that mimic industrial conditions. Applying these guidelines will improve enzyme screening efficiency, increase data reproducibility, deepen the understanding of interfacial biocatalysis, and ultimately accelerate the development of more robust and cost-effective bio-based PET recycling methods.